The Dance of Life - Ellis, Havelock, 1859-1939 (Salt Lake City, UT : Project Gutenberg, 2021)
"The Dance of Life" by Havelock Ellis is a philosophical treatise written in the early 20th century. The work explores the concept of life as an intricate art form, emphasizing the interconnectedness of various aspects of human experience, including art, religion, morality, and love. The author delves into how these elements intertwine to create the rich tapestry of life, arguing that the perception of life as a dance can lead to deeper understanding and appreciation of existence. The opening of the book introduces readers to Ellis's reflection on the nature of life and its inherent artistic qualities. He discusses how the roots of this artistic conception stem from ancient philosophies and traditions, particularly within the realms of dance and movement. The text highlights the importance of rhythm, form, and beauty in both life and art, suggesting that life is not merely to be lived but experienced as a continuous dance. Through various examples, Ellis sets the stage for further exploration of how different cultures perceive and express their existence through practices that encompass both the sacred and the mundane, promoting a holistic view of life as an art form that combines personal expression with collective cultural significance. (This is an automatically generated summary.)
Introduction -- The art of dancing -- The art of thinking -- The art of writing -- The art of religion -- The art of morals -- Conclusion.
Release date is 2021-06-27
Tim Lindell, David King, and the Online Distributed Proofreading Team at http://www.pgdp.net. (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Philosophy; Ethics; Conduct of life; English essays -- 20th century